Tabot Festival of Bengkulu and Local Wisdoms - Rifanto bin Ridwan (AJIS: Academic Journal of Islamic Studies, 2016)
Tabot is a series of rituals to commemorate the martyrdom of Hussein bin Ali bin Abi Talib who died in an unbalance war against the army of Yazid bin Muawiyah in The Battle of Karbala. At first, Tabot Festival was a religious ritual affiliated to Shia. It was first brought by Sheikh Burhanuddin known as Imam Senggolo in 1685. There are many similarities between Tabot in Bengkulu and Ta’ziyeh ritual celebrated by the followers of Shia in Persia and other countries that have many adherents of Shia. However, their relationship was limited to common history and the execution time only, while in terms of politics and religion, there is no connection between the two Over time, there is a shift in the meaning of Tabot, from religious ritual became a cultural festival in Bengkulu. There are some people who question the authenticity of Tabot and consider that it deviates the teachings of religion. However, the study found that the Tabot Festival is no longer belong to a particular individual or group, but it has become a common property of Bengkulu society. It has become a cultural heritage that must be preserved. Keywords: tabot, Bengkulu, local wisdom